"Methodological analysis of the use of interactive technologies in the process of training bachelors of vocational education for the oil and gas industry" - Antonenko, N.; Prokopenko, O.; Rudenko , Ya. (Problems of Engineer-Pedagogical Education, 2022)
The paper presents materials demonstrating the results of the introduction of intensive methods in the process of training bachelors of vocational education in the specialty "Extraction, processing and transportation of minerals" under the educational program "Vocational Education (Oil and Gas Business)" in order to increase the efficiency of the educational process. The requirements of employers put forward to the staff of oil and gas enterprises are analyzed, and it is shown how they are taken into account within the process of training higher education students at the Department of Automation, Metrology and Energy Efficient Technologies of Ukrainian Engineering Pedagogics Academy. It has been substantiated that the use of interactive forms and methods in the educational process ensures the maximum efficiency in obtaining knowledge by higher education students, forming their professional competencies, and developing their personal qualities. The relationship between the use of interactive technologies during lectures and practical classes in the course "Technical diagnostics and extension of the resource of oil and gas facilities" and the level of effectiveness of the formation of professional competencies of graduates and their compliance with the requirements of certain employers is shown. An analysis of the features of designing and conducting classes using intensive technologies, i.e. interactive lectures and case studies in practical classes within the course "Technical diagnostics and extension of the resource of oil and gas facilities", has been conducted. The analysis of the results of their implementation in the educational process is presented. The advantages of using active methods in the creation and implementation of a system for training bachelors of vocational education for the oil and gas industry are shown. The relevance of the creation and implementation of the considered technologies in the organization of the educational process in other disciplines of the educational program is substantiated. It is shown that this form of conducting training sessions in special disciplines ensures the effectiveness of the formation of professional competencies of graduates and their compliance with the requirements of certain employers.